Imprint of Initial Education and Loss of Ly49C/I in Activated Natural Killer Cells of TAP1-KO and C57BL/6 Wildtype Mice - Patil, Neha D.; Domingues, Olivia; Masquelier, Cécile; Theresine, Maud; Schlienger, Oceane; Njinju Amin Asaba, Clinton; Thomas, Marine; Seguin-Devaux, Carole; Slevogt, Hortense; Ollert, Markus; Zimmer, Jacques (Frontiers in Immunology, 2022)
Natural killer (NK) cells are important effectors of the innate immune system and participate in the first line of defense against infections and tumors. Prior to being functional, these lymphocytes must be educated or licensed through interactions of their major histocompatibility complex class I molecules with self-specific inhibitory receptors that recognize them. In the absence of such contacts, caused by either the lack of expression of the inhibitory receptors or a very low level of major histocompatibility complex class I (MHC class I) proteins, NK cells are hyporesponsive at baseline (ex vivo). After activation however, they can become cytotoxic and produce cytokines. This is particularly the case in transporter associated with antigen processing (TAP)-deficient mice, which we investigated in the present study. Transporter associated with antigen processing transports endogenous peptides from the cytosol to the endoplasmic reticulum, where they are loaded on nascent MHC class I molecules, which then become stable and are expressed at the cell surface. Consequently, TAP-KO mice have very low levels of MHC class I expression. We present a study about phenotypic and functional aspects of NK cells in four mouse strains, B6 wildtype, TAP1-KO, B6CAST and MR1-KO, in spleen and lung. We observed that in the latter as well as in wildtype mice on the same genetic background, the initial pattern of education, conferred to the cells via the inhibitory receptors Ly49C/I and NKG2A, was maintained even after a strong stimulation by the cytokines interleukin-2, interleukin-12, interleukin-15 and interleukin-18. Furthermore, the percentages of activated NK cells expressing Ly49C/I were strongly downmodulated under these conditions. We completed our investigations with phenotypic studies of the NK cells of these mice and compared them with C57BL/6CAST and MR1-knockout animals. The latter are almost devoid of mucosal-associated invariant T (MAIT) cells, but their NK cells have never been investigated in detail before. Despite the fact that MR1 structurally resembles MHC class I molecules, we could not detect major differences between MR1-KO and wildtype NK cells, suggesting a normal NK cell educational process in the context of the MR1-depleted environment.